Pelatihan Dan Pemanfaat Teknologi Informasi Dalam Pengelolaan Data Penimbangan Bayi Di Posyandu Camar Pondok Bahar Karang Tengah - Sejati Waluyo; Ika Susanti; Ferdiansyah (CV. Multi Kreasi Media, 2023)
Posyandu Camar is located in Pondok Bahar, Karang Tengah sub-district. This Posyandu has a very important role for public health, especially reducing infant mortality and improving the health of babies. The process that is routinely carried out in order to reduce the death rate and improve the health of babies is carrying out the process of weighing babies and checking baby health. Manually recording baby data is considered less effective when evaluating baby health, because the data is scattered and it is difficult to collect old data. So the community service that the author is currently carrying out is training and developing a computer-based system for managing baby weighing and recording data at the seagull posyandu in Pondok Bahar, Karang Tengah sub-district. The result of this PKM is education about the importance of using information technology in managing seagull posyandu data as well as an effective system that can be used to record and collect data on baby weighing data so that data can be easily evaluated if it is needed in the future.